2017
DOI: 10.17759/psylaw.2017060202
|View full text |Cite
|
Sign up to set email alerts
|

Social representations and information security of children and adolescents: the point of view of teachers (Part 2)

Abstract: The purpose of the presented study is to analyze the social representations about the information security of children and adolescents in groups of teachers. The study is based on the ideas of the social representations theory, in particular, on the connection between social practices and social representations. The object of the study was teachers of secondary schools, the sample was 102 people aged 22 to 65 years, (M = 39.36 years, SD = 11.12 years, 91 women and 11 men). As a matter of the experience of scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Further study of the problem in groups of children's and adolescents' immediate environment (parents and teachers) has revealed that parents and teachers understand the threat in a similar way but differ in understanding how to counter it. In particular, in a group of parents, resistance to threat is represented primarily through control and restriction of children's access to threatening information; in a group of teachers, resistance to threat is represented through prohibitions on using new media and principles of child-rearing (Bovina I. B., Budykin S. V., Dvoryanchikov N. V., Gayamova S.…”
Section: Introductionmentioning
confidence: 99%
“…Further study of the problem in groups of children's and adolescents' immediate environment (parents and teachers) has revealed that parents and teachers understand the threat in a similar way but differ in understanding how to counter it. In particular, in a group of parents, resistance to threat is represented primarily through control and restriction of children's access to threatening information; in a group of teachers, resistance to threat is represented through prohibitions on using new media and principles of child-rearing (Bovina I. B., Budykin S. V., Dvoryanchikov N. V., Gayamova S.…”
Section: Introductionmentioning
confidence: 99%